Hubungan antara Self Esteem dengan Social Anxiety pada Remaja Berstatus Sosial Ekonomi Rendah - Andhika Anggawira; Dwike Nur Kholiza; Herio Rizki Dewinda (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2022)
This study aims to determine the relationship between Self Esteem and Social Anxiety in Adolescents with Low Socioeconomic Status in SMA N 1 Talamau. The independent variable in this study is Self Esteem and the dependent variable is Social Anxiety. The measuring instrument used in this study is the Self Esteem and Social Anxiety scale. The sampling technique in this study used a purposive sampling technique. The sample in this study amounted to 53 students of SMA N 1 Talamau. Validity and reliability tests in this study used Alpha Cronbach technique. The item difference index on the Self Esteem scale moves from rix = 0,376 to rix = 0,734 with a reliability coefficient of α = 0,937 while on the Social Anxiety it moves from rix = 0,396 to rix = 0,798 with a reliability coefficient equal to α = 0,945. Based on data analysis, it can be concluded that there is a significant relationship between Self Esteem and Social Anxiety, with a correlation value (r) of -0.718 with a significant level of 0.000, which means that the hypothesis is accepted. This shows that there is a significant negative relationship between Self Esteem and Social Anxiety in Adolescents with Low Socioeconomic Status in SMA N 1 Talamau.